Thermoacoustic cooling of loudspeaker-driven synthetic jet actuator - Liu Liu; Geng Chen (Case Studies in Thermal Engineering)
To address the issue of declined cooling performance caused by the recirculation of hot jet flow into the cavity of conventional synthetic jet actuators, a loudspeaker-driven thermoacoustic-cooling synthetic jet actuator was developed by integrating a thermoacoustic cooler with a synthetic jet actuator. The acoustic and thermal characteristics of the actuator were investigated, with particular emphasis on the effect of the loudspeaker driving frequency. Experimental results show that the actuator can simultaneously generate a synthetic jet and induce thermoacoustic cooling within the porous stack. Optimal cooling is achieved by leveraging acoustic resonance through tuning the driving frequency of loudspeaker to the natural frequency of the actuator. Under resonant conditions, the actuator reached a maximum temperature drop of 5.18 °C and a peak velocity magnitude of 24.44 m/s from the orifice. This work presents a novel strategy for enhancing the cooling efficiency of synthetic jet actuators and broadens the application of thermoacoustic technology in the field of thermal management.